The Role of Work Motivation in Mediating the Influence of Work Engagement on Job Satisfaction of Cooperative Employees Consumers of Cu Sang Timur Banyuwangi - Benedictus Revan Krisnanto; Ni Wayan Mujiati (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
The role of work motivation as a mediator of the influence of work engagement on job satisfaction is important in the context of human resources. In today's globalization era, competition between companies is getting stronger, so that companies are asked to be able to get it and optimize these variables in arrange to make strides their execution and competitiveness. Hence, this inquire about points to analyze the relationship between work engagement, work motivation, and job satisfaction. This inquire about was conducted by the Shopper Agreeable of CU Sang Timur with a add up to test of 70 workers who were decided based on immersed inspecting. Information were collected through interviews that conveyed surveys to investigate subjects. Information were analyzed utilizing way examination strategies with SPSS. This inquire about points to analyze the mediating role of work motivation on the impact of work engagement on job satisfaction. The comes about of this think about demonstrate that work engagement and work inspiration altogether impact job satisfaction with a positive relationship course, work engagement essentially impacts work motivation with a positive relationship heading, and work motivation can be a arbiter of the impact of work engagement on job satisfaction in part. The suggestions of this investigate hypothetically back the discoveries of past investigate results. The practical implications of the Consumer Cooperative of CU Sang Timur are to maintain work satisfaction, work engagement, and work motivation owned by its employees.